Post-COVID-19 sequelae - Uthara Vijai Kumar (Indian Journal of Respiratory Care, 2021)
COVID-19 is a new disease and the acute clinical presentation is mostly clear now. It is also known now that the disease may have sequelae affecting various systems. The respiratory sequelae include pulmonary fibrosis due to the immune-mediated mechanisms that follow a cytokine storm, diffuse alveolar damage, and microvascular thrombosis. A decline in lung function may be seen in patients who still have residual symptoms and hypoxia. COVID-19-associated pulmonary aspergillosis, a well-recognized complication, especially in patients with acute respiratory distress syndrome, has emerged as a significant risk factor for increased mortality. Fatigue is a common symptom that patients come back with, in the post-COVID period. Dyspnea without hypoxia has been attributed to respiratory muscle dysfunction and deconditioning resulting in decreased exercise tolerance. Palpitation is another common persisting symptom. Thromboembolic disease, a common association during the acute phase of illness, is not an uncommon entity that is seen even after “recovery” from COVID-19. Thromboembolic events causing stroke have been identified as an immediate complication of COVID-19, but can occur during the recovery phase as well, in high-risk patients. The return of smell and taste sensations could take a few weeks to months even after complete recovery from the illness. Mood swings, anxiety, and sleep deprivation have all been reported by patients recovering from this viral illness. The last 14 months have been feverishly spent in trying to understand this particular disease, but the long-term complications of COVID-19 are still elusive.